My question is about proving the Lyapunov CLT (every mean is $0$, $\delta = 1$). It is similar to this question but without any assumption about the random variables following Bernoulli distributions.

The idea is to use Taylor's expansion: $\psi_{X_1}(t) = 1 - \frac{1}{2}\mathbb{E}X_1^2t^2 - \frac{i}{6}\mathbb{E}X_1^3t^3 + o(t^3)$.

Like in the Wikipedia entry, define $s_n^2 = \Sigma_{i = 1}^n\sigma_i^2$. Then $\psi_{X_1}(\frac{t}{s_n}) = 1 - \frac{1}{2}\mathbb{E}X_1^2\frac{t^2}{s_n^2} - \frac{i}{6}\mathbb{E}X_1^3\frac{t^3}{s_n^3} + o(\frac{t^3}{s_n^3})$.

If Lyapunov's condition ($\delta = 1$) is satisfied, I see that $\lim_{n\rightarrow\infty}\psi_{X_1}(\frac{t}{s_n}) = 1 - \frac{1}{2}\mathbb{E}X_1^2\frac{t^2}{s_n^2} + o(\frac{t^3}{s_n^3})$.

Define $S_n = X_1 + \dots + X_n$. If the random variables were i.i.d., then after scaling to make variances be $1$, $\psi_{\frac{S_n}{\sqrt{n}}}$ involves raising a Taylor expansion to the power of $n$. But as the random variables are non-identically distributed, $\psi_{\frac{S_n}{s_n}}$ is a product of $n$ terms. How do I manipulate it so that I can use $e^x = \lim_{n\rightarrow\infty}(1 + \frac{x}{n})^n$?

(How do you turn division by $s_n^2$ into division by $n$, which happens by squaring $\sqrt{n}$ in the i.i.d. case?)

  • $\begingroup$ Possibly you can rewrite $\prod (1-a_i t/n + O(t^2/n^2))$ as a Taylor series in a similar fashion as en.m.wikipedia.org/wiki/… $\endgroup$ Nov 29, 2023 at 10:43
  • 2
    $\begingroup$ You may follow the outline in the proof of Theorem 27.2 in Probability and Measure (3rd edition) -- or any rigorous probability book that proves the Lindeberg CLT. The problem boils down to prove the asymptotic identity (after rescaling) $\prod_{k = 1}^n(1 - \frac{1}{2}t^2\sigma_k^2) + o(1) = e^{-t^2/2} + o(1)$, which can be established by the Lyapunov's condition and the inequality $|z_1 \cdots z_m - w_1 \cdots w_m| \leq \sum_{k = 1}^m|z_k - w_k|$ when $|z_k| \leq 1, |w_k| \leq 1$. $\endgroup$
    – Zhanxiong
    Nov 29, 2023 at 13:14

1 Answer 1


The goal is to show that if $\{X_1, \ldots, X_n, \ldots\}$ is a sequence of independent random variables with zero mean and finite third moments and satisfy \begin{align*} \lim_{n \to \infty} \frac{1}{s_n^3}\sum_{k = 1}^nE[|X_k|^3] = 0, \tag{1}\label{1} \end{align*} where $s_n^2 = \sum_{k = 1}^nE[X_k^2] =: \sum_{k = 1}^n\sigma_k^2$, then \begin{align*} \frac{S_n}{s_n} \to_d N(0, 1), \tag{2}\label{2} \end{align*} where $S_n = X_1 + \cdots + X_n$.

To begin the proof, it is standard to first normalize $X_k$ as $Y_k := X_k/s_n$ so that the condition $\eqref{1}$ becomes \begin{align*} \lim_{n \to \infty} \sum_{k = 1}^nE[|Y_k|^3] = 0. \tag{3}\label{3} \end{align*} And the target $\eqref{2}$ becomes \begin{align*} Y_1 + \cdots + Y_n \to_d N(0, 1). \tag{4}\label{4} \end{align*} In addition, if denote $E[Y_k^2]$ by $\tau_k^2$, then clearly $\sum_{k = 1}^n \tau_k^2 = 1$.

Denote the characteristic function of $Y_k$ by $\varphi_k(t) := E[e^{itY_k}]$, $k = 1, \ldots, n$, it follows by Levy's continuity theorem and $\varphi_{N(0, 1)}(t) = e^{-t^2/2}$ that $\eqref{4}$ is equivalent to \begin{align*} \lim_{n \to \infty} \prod_{k = 1}^n \varphi_k(t) = e^{-t^2/2} \tag{5}\label{5} \end{align*} for every $t \in \mathbb{R}$, which will be proved as follows.

To prove $\eqref{5}$, we need the following well-known inequality that bounds $\left|\varphi_k(t) - (1 - \frac{1}{2}t^2\tau_k^2)\right|$ (which is a corollary of the basic inequality $\left|e^{ix} - (1 + ix - \frac{1}{2}x^2)\right| \leq \min\left(|x|^2, \frac{1}{6}|x|^3\right)$): \begin{align*} \left|\varphi_k(t) - \left(1 - \frac{1}{2}t^2\tau_k^2\right)\right| \leq E\left[\min\left(|tY_k|^2, \frac{1}{6}|tY_k|^3\right)\right] \leq \frac{1}{6}|t|^3 E[|Y_k|^3]. \tag{6}\label{6} \end{align*}

$\eqref{3}$ and $\eqref{6}$ together then imply \begin{align*} \sum_{k = 1}^n\left|\varphi_k(t) - \left(1 - \frac{1}{2}t^2\tau_k^2\right)\right| \to 0 \tag{7}\label{7} \end{align*} as $n \to \infty$.

Having made these preparations, $\eqref{5}$ follows from (justifications for each step can be found in the addendum): \begin{align*} & \left|\prod_{k = 1}^n \varphi_k(t) - e^{-t^2/2}\right| \\ =& \left|\prod_{k = 1}^n \varphi_k(t) - \prod_{k = 1}^ne^{-t^2\tau_k^2/2}\right| \tag{8.1}\label{8.1} \\ \leq & \left|\prod_{k = 1}^n \varphi_k(t) - \prod_{k = 1}^n\left(1 - \frac{1}{2}t^2\tau_k^2\right)\right| + \left|\prod_{k = 1}^n\left(1 - \frac{1}{2}t^2\tau_k^2\right) -\prod_{k = 1}^ne^{-t^2\tau_k^2/2}\right| \tag{8.2}\label{8.2} \\ \leq & \sum_{k = 1}^n\left|\varphi_k(t) - \left(1 - \frac{1}{2}t^2\tau_k^2\right)\right| + \sum_{k = 1}^n\left|\left(1 - \frac{1}{2}t^2\tau_k^2\right) - e^{-t^2\tau_k^2/2}\right| \tag{8.3}\label{8.3} \\ \to & 0. \tag{8.4}\label{8.4} \end{align*} This completes the proof.


$\eqref{8.1}:$ This is because $\sum_{k = 1}^n\tau_k^2 = 1$.

$\eqref{8.2}:$ Triangle inequality.

$\eqref{8.3}:$ This is the consequence of the following inequality: if $z_1, \ldots, z_m$ and $w_1, \ldots, w_m$ are complex numbers of modulus at most $1$, then \begin{align*} |z_1 \cdots z_m - w_1 \cdots w_m| \leq \sum_{k = 1}^m|z_k - w_k|. \end{align*} Note that this inequality applies because $\max_{1 \leq k \leq n}\tau_k^2 \to 0$ as $n \to \infty$, which is implied by the Lyapunov's condition $\eqref{3}$ (interestingly, the first inequality below is usually referred as the Lyapunov's inequality): \begin{align*} & (\tau_k^2)^{3/2} = (E[Y_k^2])^{3/2} \leq E[|Y_k|^3], \\ & \max_{1 \leq k \leq n}(\tau_k^2)^{3/2} \leq \sum_{k = 1}^n(\tau_k^2)^{3/2} \leq \sum_{k = 1}^nE[|Y_k|^3] \to 0. \end{align*}

$\eqref{8.4}:$ The first sum goes to $0$ by $\eqref{7}$, while the summand in the second sum is bounded by \begin{align*} & \left|\frac{1}{2!}(-t^2\tau_k^2/2)^2 + \frac{1}{3!}(-t^2\tau_k^2/2)^3 + \cdots \right| \\ \leq & \frac{1}{4}(t^2\tau_k^2)^2\sum_{k = 2}^\infty\frac{(t^2\tau_k^2/2)^{k - 2}}{k!} \\ \leq & \frac{1}{4}(t^2\tau_k^2)^2e^{t^2\tau_k^2/2} \\ \leq & \frac{1}{4}t^4e^{t^2}\tau_k^2\max_{1 \leq j \leq n}\tau_j^2, \end{align*} hence the second sum is bounded by (using $\sum_{k = 1}^n\tau_k^2 = 1$ again) \begin{align*} \frac{1}{4}t^4e^{t^2}\max_{1 \leq j \leq n}\tau_j^2\sum_{k = 1}^n\tau_k^2 = \frac{1}{4}t^4e^{t^2}\max_{1 \leq j \leq n}\tau_j^2, \end{align*} which converges to $0$ as $n \to \infty$ by the relation shown in justifying $\eqref{8.3}$.

  • $\begingroup$ Why do the $Y_k$ share characteristic function $e^{-t^2/2}$ (before equation 5)? $\endgroup$
    – johnsmith
    Dec 2, 2023 at 0:59
  • $\begingroup$ @johnsmith Eq. 5 doesn't say $Y_k$ share the same cf -- the cf of each $Y_k$ is $\varphi_k$. Eq. 5 just states the goal of the proof. $\endgroup$
    – Zhanxiong
    Dec 2, 2023 at 1:00
  • $\begingroup$ I mean this: "Since the characteristic function of $N(0,1)$ and $Y_k$ are $e^{-t^2/2}$". If we don't know the distribution of each $X_k$, why would we know the distribution of each $Y_k$? $\endgroup$
    – johnsmith
    Dec 2, 2023 at 3:18
  • $\begingroup$ @johnsmith You did not finish reading the complete sentence.... $\endgroup$
    – Zhanxiong
    Dec 2, 2023 at 3:27
  • 1
    $\begingroup$ That sentence means: Denote the characteristic function of $Y_k$ by $\varphi_k$, so that to prove $Y_1 + \cdots + Y_n \to_d N(0, 1)$ is equivalent to prove $\prod_{k = 1}^n \varphi_k(t) \to e^{-t^2/2}$. Is it clear now? (there is nothing I "deduced" about $Y_k$, it is just about how I named the cf of $Y_k$). $\endgroup$
    – Zhanxiong
    Dec 2, 2023 at 4:31

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.